PENGARUH PERILAKU BERTANGGUNG JAWAB DAN PEMAHAMAN SISWA SMA DI DKI JAKARTA TERHADAP KETAHANAN SOSIAL EKOLOGIS LOKAL - samadi, Dr (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2018)
This study aims to determine empirically the influence of responsible behavior toward ecological social resilience in the framework of environmental education in senior high school students. The research was conducted during August-December 2017. This research used experimental method with 2 X 2 factorial design. The population in this study is the affordable population with random sampling method. The test of statistical hypothesis used ANAVA (analysis of variance) by comparing the Fcount with Ftable on each treatment factor (A and B), and interaction between factors (Ax B). Data analysis in this study using Pearson correlation analysis and regression analysis where the normality test using Kolmogorov-Smirnov method. The result of the research concludes that the stronger the responsible behavior toward the environment, the more its ecological socio-economic resilience in the framework of applying of environmental education to high school students in DKI Jakarta. Keyword: Rresponsible behavior, Ecological social resilience, Environmental education in senior high school, Jakarta.